Valorization of Avocado Seed Wastes for Antioxidant Phenolics and Carbohydrates Recovery Using Deep Eutectic Solvents (DES) - Alexandra Del-Ca; Fernando Rodríguez-Rebelo; Beatriz Rodríguez-Martínez; Adrián Mallo-Fraga; Pablo G. Del-Río; Beatriz Gullón (MDPI AG, 2023)
Avocado seeds represent the chief waste produced in avocado processing, leading not only to environmental problems regarding its elimination but to a loss of economic profitability. In fact, avocado seeds are known as interesting sources of bioactive compounds and carbohydrates, so their utilization may reduce the negative effect produced during the industrial manufacture of avocado-related products. In this sense, deep eutectic solvents (DES) are a novel greener alternative than organic solvents to extract bioactive polyphenols and carbohydrates. The study was based on a Box-Behnken experimental design to study the effect of three factors, temperature (40, 50, 60 °C), time (60, 120, 180 min) and water content (10, 30, 50% v/v) on the responses of total phenolic (TPC) and flavonoid content (TFC), antioxidant capacity (measured as ABTS and FRAP) and xylose content in the extract. The DES Choline chloride:glycerol (1:1) was used as solvent on avocado seed. Under optimal conditions, TPC: 19.71 mg GAE/g, TFC: 33.41 mg RE/g, ABTS: 20.91 mg TE/g, FRAP: 15.59 mg TE/g and xylose: 5.47 g/L were obtained. The tentative identification of eight phenolic compounds was assayed via HPLC-ESI. The carbohydrate content of the solid residue was also evaluated, and that solid was subjected to two different processing (delignification with DES and microwave-assisted autohydrolysis) to increase the glucan susceptibility to enzymes, and was also assayed reaching almost quantitative glucose yields. These results, added to the non-toxic, eco-friendly, and economic nature of DES, demonstrate that these solvents are an efficient alternative to organic solvents to recover phenolics and carbohydrates from food wastes.